The The Relationship Between Parenting Perceptions And Student Learning Motivation Islamic Guidance And Counselling Study Program - Wulan Wulan (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze the relationship between perceptions of parenting patterns and student learning motivation in the Islamic Counseling Guidance Study Program, Faculty of Da'wah, Sultan Maulana Hasanuddin State Islamic University Banten. Parenting has a very important role in shaping student learning motivation, where the perception of good parenting can encourage students to study harder. This study uses a quantitative approach with a correlational method. The research sample consisted of 73 respondents selected through random sampling technique. Data were collected using a scale of perceptions of parenting patterns and learning motivation distributed through Google Form. Based on the results of the research found that: 1) The level of perception of Islamic Counseling Guidance students towards parental parenting is included in the “Good” category with a percentage of 67.64%, 2) Islamic Counseling Guidance students' learning motivation is included in the “Good” category with a percentage of 68.20%, and identifies that in addition to parental patterns, students' intrinsic motivation, especially in the indicator “Having a sense of responsibility” gets the highest score of 83.84% including in the very good category. 3) There is a significant and positive relationship between the perception of parenting patterns of parents and the learning motivation of students of the Islamic Guidance and Counseling Study Program, as evidenced by the correlation coefficient of 0.577 (medium category) and the value of p = 0.000 (p < 0.05). The R2 determination analysis shows that parental parenting contributes 33.3% to student learning motivation. In addition, the t-test results (tcount 5.957 > ttable 1.994) which shows Ho is rejected and Ha is accepted. Keywords: Parental. Child-Rearing Patterns, Learning Motivation, Student